“Citizen Journalism” in the Syrian Uprising: Problematizing Western Narratives in a Local Context - Al-Ghazzi, Omar (Communication Theory, 2014)
This article analyzes the term ‘citizen journalism’ against the backdrop of the Arab uprisings in order to show how it overlooks the local context of digital media practices. The first part examines videos emanating from Syria to illustrate how they blur the lines between acts of witnessing, reporting, and lobbying, as well as between professional and amateur productions, and civic and violent intentions. The second part highlights the genealogies of citizenship and journalism in an Arab context and cautions against assumptions about their universality. The article argues that the oscillation of Western narratives between hopes about digital media's role in democratization in the Arab World and fears about their use in terrorism circumscribe the theorization of digital media practices.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/comt.12047
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Décentrer l’histoire du jeu vidéo ? - Derfoufi, Mehdi (De l'autre côté, 2018)
Peut-on envisager une autre histoire du jeu vidéo ?
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Racisme et jeu vidéo - Derfoufi, Mehdi (Éditions de la Maison des sciences de l'homme, 2021)
En 2007, le monde du jeu vidéo est secoué par une violente polémique au sujet du jeu vidéo Resident Evil 5. Ce dernier est accusé de faire commerce du racisme, en invitant à se glisser dans la peau d'un américain blanc body-buildé, missionné dans une région africaine anonyme, et tuant des dizaines d'hommes et de femmes noires présentées comme de dangereux zombies infectés du virus T. Depuis, la communauté des joueurs et joueuses de jeux vidéo interpelle régulièrement les créateurs et créatrices des jeux sur les questions du racisme et du sexisme.Dans son ouvrage, Mehdi Derfoufi analyse les rapports de force qui structurent l'industrie du jeu vidéo, dévoilant comment le racisme se niche parfois insidieusement au cœur de scénarios de jeux vidéo à succès. Il nous invite à nous questionner. Quels sont les pays qui pèsent sur les milliards d'euros du marché mondial du jeu vidéo ? Qui sont les game designers et auteurs des jeux ? Comment les représentations racistes sont-elles véhiculées à travers les personnageset les imaginaires vidéoludiques ? L'auteur nous dévoile avec brio les logiques racialisantes à l’œuvre au sein d’un marché économique très concurrentiel où des stéréotypes exotisants servent régulièrement à faire vendre un jeu. Il nous montre aussi comment la division internationale du travail et la hiérarchie économico-politique Nord/Sud pèse sur le marché du jeu vidéo et ralentit l’émergence de nouvelles représentations. Pourtant, de nombreux espoirs, notamment dans les pays du Sud participent au renouvellement de la culture geek : face aux violences racistes, la riposte s’organise.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"–Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Section: 287 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Orientalism - Said, Edward W (Penguin Books, 2019)
A groundbreaking critique of the West's historical, cultural, and political perceptions of the East that is—three decades after its first publication—one of the most important books written about our divided world. "Intellectual history on a high order ... and very exciting." —The New York Times In this wide-ranging, intellectually vigorous study, Said traces the origins of "orientalism" to the centuries-long period during which Europe dominated the Middle and Near East and, from its position of power, defined "the orient" simply as "other than" the occident. This entrenched view continues to dominate western ideas and, because it does not allow the East to represent itself, prevents true understanding. Source: Publisher
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Manufacturing Consent in Video Games—The Hegemonic Memory Politics of Metal Gear Solid V: The Phantom Pain (2015) - Hammar, Emil Lundedal (Nordlit, 2019)
In this article I argue that the structural conditions of global capitalism and postcolonialism encourage game developers to rearticulate hegemonic memory politics and suppress subaltern identities. This claim is corroborated via an application of Edward Herman and Noam Chomsky’s propaganda model to the Japanese-developed video game Metal Gear Solid V: The Phantom Pain. This case study highlights that the hegemonic articulations of colonial histories are not exclusive to Western entertainment products where instead modes of production matter in the ‘manufacturing of mnemonic hegemony’. I also propose that the propaganda model, while instructive, can be improved further by acknowledging a technological filter and the role of the subaltern. Thus, the article furthers the understanding of the relation between production and form in contemporary technological phenomena like video games and how this relation motivates hegemonic articulations of the past in contemporary mass culture.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir)

War Games: Memory, Militarism and the Subject of Play - Hammond, Philip; Pötzsch, Holger (Bloomsbury Publishing USA, 2019)
Many of today's most commercially successful videogames, from Call of Duty to Company of Heroes, are war-themed titles that play out in what are framed as authentic real-world settings inspired by recent news headlines or drawn from history. While such games are marketed as authentic representations of war, they often provide a selective form of realism that eschews problematic, yet salient aspects of war. In addition, changes in the way Western states wage and frame actual wars makes contemporary conflicts increasingly resemble videogames when perceived from the vantage point of Western audiences.This interdisciplinary volume brings together scholars from games studies, media and cultural studies, politics and international relations, and related fields to examine the complex relationships between military-themed videogames and real-world conflict, and to consider how videogames might deal with history, memory, and conflict in alternative ways. It asks: What is the role of videogames in the formation and negotiation of cultural memory of past wars? How do game narratives and designs position the gaming subject in relation to history, war and militarism? And how far do critical, anti-war/peace games offer an alternative or challenge to mainstream commercial titles?
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Video Games and the Global South - Penix-Tadsen, Phillip (ETC Press, 2019)
Redefines games and game culture from south to north, analyzing the social impact of video games, the growth of game development and the vitality of game cultures across Africa, the Middle East, Central and South America, the Indian subcontinent, Oceania and Asia.
OCLC: 1104212185
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Casual Empire: Video Games as Neocolonial Praxis - Harrer, Sabine (Open Library of Humanities, 2018)
As a media form entwined in the U.S. military-industrial complex, video games continue to celebrate imperialist imagery and Western-centric narratives of the great white explorer (Breger, 2008; Dyer-Witheford & de Peuter, 2009; Geyser & Tshalabala, 2011; Mukherjee, 2016). While much ink has been spilt on the detrimental effects of colonial imagery on those it objectifies and dehumanises, the question is why these games still get made, and what mechanisms are at work in the enjoyment of empire-themed play experiences. To explore this question, this article develops the concept of ‘casual empire’, suggesting that the wish to play games as a casual pastime expedites the incidental circulation of imperialist ideology. Three examples – Resident Evil V (2009), The Conquest: Colonization (2015) and Playing History: Slave Trade (2013) – are used to demonstrate the production and consumption of casual empire across multiple platforms, genres and player bases. Following a brief contextualisation of postcolonial (game) studies, this article addresses casual design, by which I understand game designers’ casual reproduction of inferential racism (Hall, 1995) for the sake of entertainment. I then look at casual play, and players’ attitudes to games as rational commodities continuing a history of commodity racism (McClintock, 1995). Finally, the article investigates the casual involvement of formalist game studies in the construction of imperial values. These three dimensions of the casual – design, play and academia – make up the three pillars of the casual empire that must be challenged to undermine video games’ neocolonialist praxis.
Number: 1
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Google-Books-ID: qJwRvgAACAAJ
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Transnational Contexts of Culture, Gender, Class, and Colonialism in Play: Video Games in East Asia - Pulos, Alexis; Lee, S. Austin (Palgrave Macmillan, 2016)
This book examines the local, regional and transnational contexts of video games through a focused analysis on gaming communities, the ways game design regulates gender and class relations, and the impacts of colonization on game design. The critical interest in games as a cultural artifact is covered by a wide range of interdisciplinary work. To highlight the social impacts of games the first section of the book covers the systems built around high score game competitions, the development of independent game design communities, and the formation of fan communities and cosplay. The second section of the book offers a deeper analysis of game structures, gender and masculinity, and the economic constraints of empire that are built into game design. The final section offers a macro perspective on transnational and colonial discourses built into the cultural structures of East Asian game play
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play – the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Google-Books-ID: jXjHAgAAQBAJ
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé